2017
DOI: 10.1016/s1473-3099(17)30405-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HSV-2 infection on subsequent HIV acquisition: an updated systematic review and meta-analysis

Abstract: SummaryBackgroundHIV and herpes simplex virus type 2 (HSV-2) infections cause a substantial global disease burden and are epidemiologically correlated. Two previous systematic reviews of the association between HSV-2 and HIV found evidence that HSV-2 infection increases the risk of HIV acquisition, but these reviews are now more than a decade old.MethodsFor this systematic review and meta-analysis, we searched PubMed, MEDLINE, and Embase (from Jan 1, 2003, to May 25, 2017) to identify studies investigating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
205
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(215 citation statements)
references
References 77 publications
4
205
1
5
Order By: Relevance
“…Many previous studies have documented the strong association between these 2 infections at the individual level, and this finding has been remarkably consistent across different studies and settings [4, 28]. In cross-sectional studies (including the current analysis), the direction of causality cannot be definitively established, and some or all of the association might be explained by an effect of HIV on the acquisition of HSV2 infection.…”
Section: Discussionsupporting
confidence: 77%
“…Many previous studies have documented the strong association between these 2 infections at the individual level, and this finding has been remarkably consistent across different studies and settings [4, 28]. In cross-sectional studies (including the current analysis), the direction of causality cannot be definitively established, and some or all of the association might be explained by an effect of HIV on the acquisition of HSV2 infection.…”
Section: Discussionsupporting
confidence: 77%
“…As with other systematic and meta‐analytic reviews of longitudinal studies of STI and HIV interactions, there are some limitations to our reviews that may affect our results in either direction . HPV and HIV are both STIs associated with similar sexual risk factors, which may lead to overestimation of the magnitude of STI and HIV associations.…”
Section: Resultsmentioning
confidence: 96%
“…Whilst we found that the magnitude of the association was similar by timing of HPV infection (incident, prevalent or cleared infection), differing types and density of immunological cells in the genital area could in theory translate into varying risk of HIV acquisition over the course of HPV infection and warrants further investigation. A recent systematic review and meta‐analysis of 57 studies found higher risk of HIV acquisition in those with incident HSV‐2 infection (compared to those without HSV‐2 infection) than was found for prevalent HSV‐2 infection . The interactions between HIV and HPV could be analogous to the interactions between HIV and HSV‐2 in terms of some similarity of biological mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests a direct and reciprocal biological interaction between HIV and HSV2 [46]. Additionally, HIV and HSV2 are associated with similar risk factors [age, sex, partner change, condom use and male circumcision) [46]. Thus, HSV2 may be considered a proxy measure for risky sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%